Consideration of leasing as an effective tool in the system of effective activity of industrial enterprises - Plakhotnik, Olena (Technology audit and production reserves, 2020)
In the context of the economic crisis for the development of the national economy, the need is growing for developing reliable mechanisms for attracting investments, which are a means of modernizing fixed assets and introducing the latest technologies. Due to the possibility of risk when investing in new technologies, commercial banks are not actively involved in financing the development of innovations. To a large extent, the solution of these problems can be achieved through the use of leasing, is a promising area of economic activity of industrial enterprises. Therefore, the object of research is leasing as a tool for investment and innovative development of industrial enterprises. In the work, on the basis of a systematic approach, the list of tasks, principles, and functions for the transfer of technologies in the form of leasing as a way of commercializing innovative products of industrial enterprises has been supplemented, which is aimed at enhancing their innovative activity. An approach to the definition of leasing as an effective tool in the system of effective activity of industrial enterprises is proposed. It has a number of application features, in particular, it is based on an economic-mathematical model for choosing the form of technology transfer and assessing its impact on the market value of an enterprise. A distinctive feature of the model from existing approaches is the accounting for the value of assets and the increase in the market value of assets for an investment project, which is implemented using technology transfer, as well as net discounted cash income. This allows to apply the model in the case of determining the effectiveness of bank lending as a way of financing technology transfer. The use as indicators of the model indicators of the formation of the market value of the enterprise allows to use it to model the main indicators of its property valuation by composition and sources of formation. Using this model in the practice of industrial enterprises will determine the effectiveness of leasing in the implementation of investment projects.